Diseño de estación intermodal, como eje articulador del transporte entre los municipios de Ibagué, Alvarado y espinal; a partir de los corredores férreos existentes (2023)
The present work corresponds to a degree work to opt for the title of architect, within the Faculty of Arts of the Antonio Nariño de Ibagué University. The research carried out is categorized within the type called applied research, from which it seeks to respond in a non-systematic way to specific problems. In the present case, the problem that gives rise to the investigation is framed within the dynamics of passenger mobility between the main cities of the department, as well as those of greater geographical proximity, since there is a lack of an articulating mechanism that allows organizing passenger mobility between the municipalities of Ibagué, Alvarado and Espinal. Thus, the present urban project responds to the problem with a proposal for the design of a multimodal station located in the corregimiento of Ibagué called Buenos Aires, which would have a potential annual population of 13,339,503 passengers; who demand transport between the municipalities of the circuit that has been called the Central Province of Tolima.